Analysis of Employment in The Russian Federation From 2009 to 2019 ("Journal "U". Economy. Management. Finance.", 2020)
The level of employment of the population characterizes the level of economic development of the state, so the topic of this article is relevant. The article presents an analysis of the level of employment of the working-age population in the dynamics from 2009 to 2019, as well as this economic indicator in the context of the Federal districts of the Russian Federation. Conclusions are drawn about the reasons for the decline in employment, as well as how this affects the economy of the country and a particular region.
Keywords: employment; employment rate; able-bodied population; economic crisis